INVESTIGATING DAIRY FARMERS’ RESILIENCE UNDER A TRANSFORMING POLICY AND A MARKET REGIME: THE CASE OF NORTH KARELIA, FINLAND - Rizzo, Fulvio (Quaestiones Geographicae, 2017)
The European dairy sector is currently facing unprecedented challenges under a transforming policy and a market regime. The expected changes will have relevant consequences for land use, the landscape, and the environment in rural areas dominated by dairy farming. Within this context, the aim of this paper is twofold. First, key characteristics of milk production in the region of North Karelia will be illustrated. Secondly, some light will be shed on dairy farmers’ challenges and adaptations to the dairy sector’s structural changes, and to what extent they contribute to the resilience of agricultural systems. In the light of an evident milk crisis, the findings suggest that farmers’ key challenge is the profitability of running a dairy enterprise. One of the consequences of the poor economic situation is the pressure to make investments in the conditions of a constantly changing policy. Flexibility and the ability to understand future trends are fundamental in adapting to socio-economic changes and unpredictability. Adaptation to unpredictability would not be possible without a key characteristic of farming activity: agriculture is not only a source of an income, but also a way of life, a sense of belonging to the land that significantly affects farmers’ decision-making.